Dobras em bainha macroscopicas relacionadas ao cisalhamento ductil de baixo angulo da nappe Araxa-Canastra no sudoeste de Minas Gerais - Simoes, L. S D A (My University, 1993)
In the Proterozoic fold-thrust belt of Southwestern Minas Gerais, sheath folds belonging to Araxa-Canastra Group were mapped. These structures are explained by a tangential shear related to nappe transport, which acted together with an additional transcurrent shear, driven by a lateral ramp. An interesting feature recognized in these sheath folds is the striking obliquity between the hinge line of the macro structure and the hinge lines of the parasitic folds in the sheath fold closure. -English summary
Macroscopic sheath folds related to the low-angle ductile shear of Araxa-Canastra nappe in the southwest Minas Gerais
Keywords: deformation; folding; nappe; Proterozoic; sheath fold; Brazil, Minas Gerais